Short-term alterations of brain network properties in subthreshold depression: the impact of Internet-based Cognitive Behavioral Therapy - Wenquan Yu; Yuchen Ying; Li Wang; YiLing Yang; Li Zhang; Yu Wang; Zili Zhu; Hui Zhang; Yuning Pan (Frontiers in Neurology)
PurposePatients with subthreshold depression (sD) carry a significant risk of developing major depressive disorder. However, few studies focus on the influence of Internet-based Cognitive Behavioral Therapy (ICBT) on brain network, particularly among Chinese undergraduates. This study aims to conduct resting-state functional MRI (rs-fMRI) to explore the effects of ICBT on neurofunctional network.MethodsThis short-term longitudinal study enrolled 30 sD patients and 24 healthy matched participants. We gathered the clinical measurements outcomes from sD patients. Baseline and post-intervention MRI scans were performed for the sD patients, additionally, a matched healthy controls group underwent baseline MRI scans, functional network matrix was established from the temporal rs-MRI series. Nodal efficiency (Enod) was quantified by calculating the area under the curve (AUC) of network metrics.ResultsThe patients with sD exhibited reduced clinical measurement scores after ICBT intervention. Moreover, after ICBT intervention, functional network analysis revealed an increased Enod in the orbital part of the left inferior frontal gyrus, and decreased Enod in the left paracentral lobule and right precentral gyrus.ConclusionThis study showed alterations in brain network in patients with sD after ICBT intervention. These findings shed light on the neurofunctional mechanisms underlying the effects of ICBT in sD patients.